3D printed osteochondral scaffolds: design strategies, present applications and future perspectives - Liu, Ge; Wei, Xiaowei; Zhai, Yun; Zhang, Jingrun; Li, Junlei; Zhao, Zhenhua; Guan, Tianmin; Zhao, Deiwei (Frontiers in Bioengineering and Biotechnology, 2024)
Articular osteochondral (OC) defects are a global clinical problem characterized by loss of fullthickness articular cartilage with underlying calcified cartilage through to the subchondral bone. While current surgical treatments can relieve pain, none of them can completely repair all components of the OC unit and restore its original function. With the rapid development of threedimensional (3D) printing technology, admirable progress has been made in bone and cartilage reconstruction, providing new strategies for restoring joint function. 3D printing has the advantages of fast speed, high precision, and personalized customization to meet the requirements of irregular geometry, differentiated composition, and multi-layered boundary layer structures of joint OC scaffolds. This review captures the original published researches on the application of 3D printing technology to the repair of entire OC units and provides a comprehensive summary of the recent advances in 3D printed OC scaffolds. We first introduce the gradient structure and biological properties of articular OC tissue. The considerations for the development of 3D printed OC scaffolds are emphatically summarized, including material types, fabrication techniques, structural design and seed cells. Especially from the perspective of material composition and structural design, the classification, characteristics and latest research progress of discrete gradient scaffolds (biphasic, triphasic and multiphasic scaffolds) and continuous gradient scaffolds (gradient material and/or structure, and gradient interface) are summarized. Finally, we also describe the important progress and application prospect of 3D printing technology in OC interface regeneration. 3D printing technology for OC reconstruction should simulate the gradient structure of subchondral bone and cartilage. Therefore, we must not only strengthen the basic research on OC structure, but also continue to explore the role of 3D printing technology in OC tissue engineering. This will enable better structural and functional bionics of OC scaffolds, ultimately improving the repair of OC defects.